Flatsonic Ultrasonic Tip Optimizes the Removal of Remaining Filling Material in Flattened Root Canals: A Micro–computed Tomographic Analysis - Santos-Junior, Airton Oliveira [UNESP]; Tavares, Karina Ines Medina Carita [UNESP]; Pinto, Jáder Camilo; Torres, Fernanda Ferrari Esteves; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mário [UNESP] (Elsevier, 2024)
Introduction: The aim of this study was to evaluate the effectiveness of the XP-endo Finisher R (XPFR; FKG Dentaire, La Chaux-de-Fonds, Switzerland) or the Flatsonic ultrasonic tip (Helse Ultrasonic, Santa Rosa de Viterbo, SP, Brazil) in removing remaining filling material after the retreatment of flattened root canals using micro–computed tomographic imaging. Methods: Twenty-four flattened distal root canals of mandibular molars with a buccolingual diameter 4 or more times larger than the mesiodistal diameter were prepared with Reciproc Blue (RB) R40 (VDW GmbH, Munich, Germany) and filled using the Tagger hybrid technique. All canals were retreated with RB R40, and apical enlargement was performed with RB R50 (VDW GmbH). The specimens were randomly distributed into 2 groups: XPFR or Flatsonic (n = 12). The percentage of remaining filling material after retreatment and centralization ability was evaluated. Data were submitted to Mann-Whitney, Wilcoxon, and unpaired t tests (α = 5%). Results: Greater capacity to remove remaining filling material in the entire canal and the cervical and middle thirds was observed for the Flatsonic compared with the XPFR (P < .05). However, both supplementary cleaning techniques showed a similar percentage of residual filling material in the apical third (P > .05). No difference was observed in the centralization ability between the techniques (P > .05). Conclusions: The Flatsonic promotes greater removal of remaining filling material than the XPFR in the retreatment of flattened root canals. However, both supplementary cleaning approaches were similar in the apical third. The XPFR and Flatsonic were able to maintain root canal centralization.
Keywords: Endodontic retreatment; flattened root canals; micro–computed tomography; ultrasonics